Low Molecular Weight Heparin (Enoxaparin) Induced Hematuria in covid-19 Patients, Experience at a Covid Dedicated Hospital (Bangladesh Journal of Urology, 2023)
Introduction: The nightmare of Covid -19 is still not over, due to its antigenic diversity. Covid produces a hypercoagulable state and results in thrombosis which is one of the leading causes of death of Covid 19 patients. Low molecular weight heparin (LMWH)- enoxaparin has proven the benefit of reducing morbidity and mortality by reducing the thrombotic effect. But unfortunately, this anticoagulant can result haematuria and unnecessary hemorrhagic manifestation that may require immediate intervention. The exact scenario of enoxaparin-induced hematuria in the covid patient is still not explored by standard high-volume study.Objective: Determine the incidence of hematuria by enoxaparin (LMWH) in covid-19 patients.Material and method: The study was conducted over 210 cases for 6 months duration. Indoor patients receiving subcutaneous enoxaparin who tested positive for Covid19-RTPCR or who had signs of Covid in chest CT (Computerized Tomography) were enrolled. Both microscopic and gross haematuria cases were included in the current study.Result: Out of 210 patients, only 5 patients (2.38%) developed haematuria. 2 had only microscopic and 3 had gross haematuria. Out of them, 3(60%) were male and 2(40%) were female. Hematuria was more common in those who received a higher dosage of enoxaparin.Conclusion: This study found that enoxaparin-induced haematuria in the covid patient is not uncommon, and hematuria is significantly higher in patients receiving higher doses. Further high-volume study is recommended on this issue.Bangladesh J. Urol. 2022; 25(2): 76-79